2015
DOI: 10.1002/cphc.201500283
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Extraction of Uranium (VI) from Nitric Acid Solution into an Ionic Liquid by using Tri‐n‐butyl phosphate

Abstract: We present new results on the liquid-liquid extraction of uranium (VI) from a nitric acid aqueous phase into a tri-n-butyl phosphate/1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (TBP/[C4 mim][Tf2 N]) phase. The individual solubilities of the ionic-liquid ions in the upper part of the biphasic system are measured over the whole acidic range and as a function of the TBP concentration. New insights into the extraction mechanism are obtained through the in situ characterization of the extracted ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…On the basis of the UV-vis spectrophotometric data, and taking advantage of the previous studies, [17] we suggest that at low acidities the extraction the behavior is explained in terms of the double cation-exchange mechanism as shown in Eq. (2): [9,10]…”
Section: Proposed Extraction Mechanismmentioning
confidence: 67%
See 3 more Smart Citations
“…On the basis of the UV-vis spectrophotometric data, and taking advantage of the previous studies, [17] we suggest that at low acidities the extraction the behavior is explained in terms of the double cation-exchange mechanism as shown in Eq. (2): [9,10]…”
Section: Proposed Extraction Mechanismmentioning
confidence: 67%
“…[18] In addition to the influence of slight changes in the alkyl chain length on the imidazolium cation (from 4 to 5) and in the TBP concentration (from 1.1 M to 1.2 M) from one experiment to the other, we think that this difference in the D values is mainly due to the change in the IL anion, from PF 6 for the work of Giridhar [16] to NTf 2 for the other two works. [17,27] In a separate study, Giridhar et al reported a D U value of ca. 6 under identical conditions (i.e., with 1.1 M TBP in [C 4 mim][NTf 2 ] at 4 M HNO 3 ), [28] which is close to the values of Billard and Dietz in the same IL (see Table 3).…”
Section: Extraction Kinetics In Rtilmentioning
confidence: 96%
See 2 more Smart Citations
“…As discussed below, the extraction of the metal ions was independent of nitrate ion concentration suggesting that the lowering in the D values with increasing HNO 3 concentration could only be explained by an increasing tendency of the extraction of H + ion towards the ionic liquid phase with increasing HNO 3 concentration (as HL + species) thereby making the metal ion extraction as a competing reaction and hence, becoming less important at higher nitric acid concentrations. Such competing cation‐exchange mechanism where the H + ion gets extracted into ionic liquid medium is well known but not relevant in molecular diluents. The extraction equilibrium defining a cation‐exchange mechanism is given as: normalM normalaq 3+ + normalxL normalIL +3 normalC normal4 normalmim normalIL + K ex M (L) x IL 3+ +3 normalC normal4 normalmim normalaq + while that involving a solvation or ion‐pair mechanism is given as: normalM normalaq 3+ +3 normalNO 3 aq + normalxL normalorg K ex [M ( normalNO 3 ) 3 Lx] normalorg where the subscripts “aq” and “IL” represent species those in the aqueous and in the RTIL phases, respectively.…”
Section: Resultsmentioning
confidence: 99%